INDONESIA’S INTRA -INDUSTRY TRADE WITH ASEAN - Agus Widarjono (Universitas Islam Indonesia, 2008)
AFTA has been starting since 2003. This study will investigate Indonesia’s bilateral trade with ASEAN member by examining intra-industry trade. The Grubel-Lloyd Index is applied to measure intra-industry trade. Intra –industry trade is classified based on factor intensity in the production process. There are natural resource intensive, unskilled labor intensive, physical capital intensive, human capital intensive and technological intensive. This research shows that level of Indonesia’s intra-industry trade with ASEAN-4 has increased rapidly since 1995. In particular, intra-industry trade level of physical capital intensive (PCI) and technology intensive (TI) is relatively high. An intra-industry trade level of human capital intensive (HCI) and unskilled labor intensive is at medium level. Meanwhile, intra-industry trade level of natural resources industry (NRI) tends to decrease.Keywords: Intra Industry Trade, Inter Industry Trade and Grubel-Llyod Index.